Virtual Rural Secondary Education in Río Negro, Argentina: an experience of more than 10 years (Praxis Educativa, 2022)
This work aims to provide a historical overview, description and analysis of the development of the Virtual Rural Secondary Education experience. Pluriaño, of more than a decade, in the Province of Río Negro. They develop: the characteristics of the rural context, the structure of the level and modality, the general objectives, the regulations, the functional plant, social and instrumental mediations, technological resources and connectivity.The proposal was presented in 2010, as an alternative that would make access, permanence and graduation possible. Includes voices of the protagonists, results and final reflections.A regulatory, national and provincial review was carried out; bibliographic consultations, official documents, UNICEF reports, the (CELE) of the University of Palermo, the ALTEC website, the Ministry of Education and Human Rights of the province, and institutional videos.
Keywords: virtual rural secondary school; digital inclusion; instrumental and social mediations; results